Challenges and perspectives in porcine model of acute lung injury using oleic acid. (December 2019) - Borges, Aline Morás; Ferrari, Renata Sallati; Thomaz, Leonardo Dalla Giacomassa Rocha; Ulbrich, Jane Maria; Félix, Elaine Aparecida; Silvello, Daiane; Andrade, Cristiano Feijó
Abstract: The oleic acid (OA) models of lung injury try to simulate the findings of human Acute Respiratory Distress Syndrome (ARDS). However, these models are difficult to replicate because they vary in terms of animals species, OA doses, time for establishment of lung injury, different observation periods and settings of mechanical ventilation. The objective of this study was to evaluate a protocol of administration of OA in lung injury model, challenges in its development and its effects on respiratory mechanics, hemodynamic changes, histology, gas exchange and mortality. We then submitted ten Large White pigs to acute lung injury through intravenous infusion of acid oleic in the pulmonary artery. The mortality of the model was 50%, due to an intense hemodynamic instability during OA administration, even with early use of vasoactive drugs. Three animals required additional doses of OA to achieve criteria for acute lung injury. Histology showed findings consistent with acute lung injury. However, more pulmonary edema was observed in lower segments than in upper segments of both lungs (p = 0.01). IL-6 and IL-8 were significantly increased compared to normal lungs (p < 0.05), and IL-6 showed higher levels in upper segments compared to lower segments (p = 0.03). Positive cells for Caspase 3 were present in all samples, localized mainly in respiratory epithelial cells and macrophages. In conclusion, this model shows histological findings of acute lung injury and inflammatory response similar to those of clinical ARDS, it presents high mortality, inconsistent reproducibility and hardly controlled hemodynamic instability.